Effect of Pyrolysis Temperature on the Properties of Tobacco Stem Biochar and Its Adsorption of Cd2+ - Defei HE; Yufen HUANG; Xiang LI; Weisheng CHEN; Lan WEI; Qimei LIN; Zhongzhen LIU; Peng LIU (Guangdong nongye kexue)
【Objective】A large amount of tobacco stems produced in China's tobacco production is a problem that needs to be solved urgently. We prepared biochar by treatment with pyrolysis carbonization technology, and characterized its physicochemical properties to explore its adsorption properties of heavy metal Cd2+, with a view to providing a pathway and data support for the demand of resource utilization of tobacco stems.【Method】Tobacco stems were used as raw materials for the preparation of biochar and pyrolyzed at five temperatures of 300 ℃, 400 ℃, 500 ℃, 600 ℃ and 700 ℃. The effects of pyrolysis temperatures and structural properties on Cd2+ adsorption were investigated by various characterization means, indoor batch adsorption tests and adsorption kinetics tests.【Result】There were significant differences in the properties and Cd2+ adsorption characteristics of tobacco stem biochar pyrolyzed at different temperatures. The pH increased from 9.05 to 11.54 when the pyrolysis temperature was increased from 300 ℃ to 700 ℃. The H, O and N contents and the atomic ratios of H/C, O/C and (O+N)/C also decreased with the increase of pyrolysis temperature, showing that the aromatic structure of hightemperature pyrolyzed biochar was more complex and stable; the specific surface area of low-temperature tobacco stem biochar was relatively large, however, the surface pore structure was more developed at high temperature. The quasi-second kinetic equation and intra-particle diffusion equation could well fit the adsorption process of Cd2+ by different temperatures of the straw biochar, indicating that the adsorption is heterogeneous chemisorption; the high temperature pyrolysis of stems had a strong adsorption capacity for Cd2+, and the rich pore structure of its surface enhances the adsorption of Cd2+, therefore, the removal rate of Cd2+ by T700 was as high as 99.01%; with Langmuir-Freundlich fitting, the maximum adsorption amounts (Qm) ranged from 54.40 to 106.16 mg/g, with the largest Qm values for 700 ℃ biochar, which were also much higher than those for rice straw, wheat and other crop straw biochar.【Conclusion】The biochar of tobacco stem prepared at different pyrolysis temperatures has a strong adsorption capacity for Cd2+ and has the potential to be applied for remediation of environmental Cd2+ pollution in the environment.